(3GdebJUO aj TQM GdEjVGMs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3jOjGf HjVGhGf hef QO GdGe eG JbOe PcQg ef bhdg aEPG gi HYXGe hOeG aGdCUd Oei Ke OekG s
(3BNQgG (B:s
(3hGf Jchf GdGe eSGYOI dCNhGJgG ai GdGeJfGY ef GOZGegG ai Gdfhf ceG SGYOJgG ai GOZGe Gdfhf ajgG aGYQag gPG BNQ cJGH GdebJUQ ai TQM GdGjVGM s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B212s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs